Interpreting the Meaning of the Word “Lʿalla” (Arabic: لَعَلَّ, lit. maybe) in the Noble Quran and Its Effect on Understanding the Verses - Hossein Zia Tawhidi; Sayyid Hossein Sayyidi (آموزه‌های قرآنی)
The word “Lʿalla” (Arabic: لَعَلَّ, lit. hopefully, in order, so that perhaps, maybe) which is used in the Noble Quran 129 times, sometimes has a meaning in the linguistic structure of the Noble Quran, which conveys a meaning that becomes ambiguous. This word has been used in the linguistic structure of the Noble Quran in several senses, but scholars and translators has been considered only the first meaning of it in its analysis and the general translators of the Noble Quran have generally translated the term “perhaps” and “should” in general. We will attempt in this article to select the exact meaning of that word in each of the verses by determining the multiple meanings of “Lʿalla” according to the contextual meaning and criticism of the non-textual meaning. The result of this research is that “Lʿalla” has been used in the linguistic context of the Holy Quran in seven meanings: Verbal hope (Arabic: تَرَجِّی, wishing, hoping with, desire), positional hope, wishing (Arabic: تَمَنّی), reasoning (Arabic: تعلیل), questioning (Arabic: استفهام), maximum certainty and conjecture. Translators and Quranic scholars should not neglect these meanings when interpreting and interpreting the verses.